Multiple Myeloma Patients at Various Cytogenetic Risks Benefit Differently from Autologous Stem Cell Transplantation as a Consolidation Therapy - Tianmei Zeng; Lili Zhou; Hao Xi; Weijun Fu; Juan Du; Chunyang Zhang; Hua Jiang; Jian Hou (Stem Cells International)
Aim. To evaluate whether patients with multiple myeloma at various risks can still benefit the same from autologous stem cell transplantation consolidation in the era of novel agents. We retrospectively analyzed 67 consecutive myeloma patients receiving autologous stem cell transplantation after bortezomib and/or thalidomide based inductions. Totally 17 high-risk, 24 intermediate-risk, and 26 low-risk patients were enrolled, based on fluorescence in situ hybridization and ISS stage. Meanwhile, another 67 risk-, response depth-, and age-matched patients not proceeding to autologous stem cell transplantation were chosen as controls. Our preliminary data indicated that, in the high-risk subgroup, progression-free survival and overall survival were both significantly prolonged after autologous stem cell transplantation (P<0.001 and P=0.015) while, in the intermediate-risk subgroup, neither progression-free survival nor overall survival was prolonged significantly after autologous stem cell transplantation (P>0.05), and in the low-risk subgroup, only progression-free survival was extended significantly (P=0.012) after autologous stem cell transplantation. Multiple variables analysis further indicated that autologous stem cell transplantation and risk stratification were two independent prognostic factors for overall survival. Our results indicated that myeloma patients at different risks all benefit from autologous stem cell transplantation consolidation even in the era of novel agents.